The Rhetorical Moves in Indonesian EFL Thesis Abstracts across Educational Levels - Shinta Amalia; A Effendi Kadarisman; Ekaning D Laksmi (Jurnal Pendidikan Humaniora, 2018)
Abstract: This study aims at investigating the rhetorical moves and steps of 24 undergraduate and graduate thesis abstracts. It mainly focuses on how the writers demonstrate the realization of linguistics yielding the conventional and standardized abstract writing convention. This corpus-based research utilizes the descriptive qualitative design. The result of this study reveals that most thesis abstracts have accommodated five moves. Interestingly, five out of eight abstracts written by students with low-level GPA come complete five moves, but only three out of five written by high-leveled GPA students present the complete five moves. In addition, several overlapping steps occur in the moves of the abstracts regardless of their GPA level.Key Words: rhetorical moves;linguistics features;non-linguistic featuresAbstrak: Penelitian ini bertujuan untuk menyelidiki pergerakan retoris dan langkah dalam 24 abstrak tesis S1 dan S2. Fokusnya pada bagaimana para penulis menunjukkan realisasi fitur linguistik untuk menghasilkan norma penulisan abstrak yang konvensional dan berstandar. Penelitian berbasis korpus ini menggunakan desain deskriptif kualitatif. Hasil penelitian menunjukkan bahwa sebagian besar abstrak tesis telah mengakomodasi lima pergerakan. Menariknya, lima dari delapan abstrak yang ditulis oleh mahasiswa ber-IPK rendah mengandung lengkap lima langkah, namun hanya tiga dari lima abstrak yang ditulis oleh mahasiswa ber-IPK tinggi tampil lengkap dengan lima langkah. Disamping itu, beberapa langkah tampil tumpang tindih dalam pergerakan abstrak terlepas dari tingkat IPK penulisnya.Kata kunci: langkah-langkah retoris, fitur linguistik, fitur non-linguistik